Kemitraan Antara BLK dan Dunia Usaha Dunia Industri Dalam Penguatan Kompetensi Peserta Pelatihan - Nuriadi, Ika Nurida; Hendrawijaya, Arief Tukiman; Purnamawati, Frimha (JPUS: Jurnal Pendidikan Untuk Semua, 2022)
The implementation of training programs often does not match the needs of the world of work, this is due to the lack of link and match to industry needs. Therefore, a partnership is needed between training institutions and the business world and the industrial world as labor users, as one of the training agencies that establish partnerships with the business world and the industrial world is the UPT Mojokerto Job Training Center. To create a strategic partnership so as to be able to prepare a competent and qualified workforce, BLK establishes a communication forum between training institutions and industry. The purpose of this study is to identify and describe the partnership between BLK and the industrial world (DUDI) in improving the competence of training participants. This research method describes the partnership carried out by the Mojokerto BLK in the form of a partnership and the partnership implementation process. Each partnership carried out produces several forms and processes for implementing partnerships in order to improve the competence of the trainees, namely knowledge, skills and work attitudes.